Development of Bed Linen Performance Index - Messay Dubale; Hermela Ejegu; Wondwossen Mamuye; Solomon Addis (Journal of Engineering)
In order to develop the performance of the bed linen index objectively, the first seven properties of the fabric are selected by twenty-four experts subjectively, and these experts also give the weight for each property according to the necessity. These properties are total hand value (THV), moisture management, abrasion resistance, air permeability, wrinkle recovery, thermal resistance, and drape of fabric. After selecting the properties and the weight for each characteristic, an integrated index for bed linen performance value is developed. Before directly using the value of each property into the equation, normalization of data should be done to shrink the range of the data such that the range is fixed between 1 and 5. The correlation between subjective and objective evaluations was very high (r = 0.82). This indicates that the bed linen performance index could be estimated as well.